THE INFRASTRUCTURE MANAGEMENT OF THE PERI-URBAN INTERFACE WITHIN THE INTERGOVERNMENTAL COOPERATION FRAMEWORK - Hendrowati, Agustina Ratri (FIA UB, 2013)
Abstract: The Infrastructure Management of The Peri-Urban Interface Within The Intergovernmental Cooperation Framework. Urban sprawl in peri-urban more likely brings the consequences of ineffective and inefficient urban basic infrastructure provision. As a result cities need an approach of urban basic infrastructure provision to meet the effective urban governance, particularly by boosting intergovernmental cooperation. The purpose of this study is to provide a new look at the formation of an intergovernmental cooperation based on local characteristics by applying analytical hierarchy process (AHP). Research findings indicate that the combined judgment resulted that the most important problems in urban basic infrastructure provision in PUI is regulatory. Furthermore, the combined judgment showed that the most importat sector to be prioritized in urban basic infrastructure provision is road and public transportation, while the most influencing factor to be considered in cooperative scheme is clear horizontal accountability. The final finding of the study based on overall judgments made ââby informants is